Penerapan Pendekatan Behavior untuk Meningkatkan Kedisiplinan pada Pembelajaran Bahasa Indonesia Kelas VIII [The Implementation of Behavioural Approach to Enhance Discipline in Grade 8 Students During the Bahasa Indonesia Lesson] - Iko Agustina Boangmanalu; Magdalena Ega Putri (Universitas Pelita Harapan, 2021)
The purpose of writing is to describe the application of a behaviour approach in the Christian education paradigm in learning Indonesian for grade VIII to improve student discipline in doing assignments using descriptive qualitative methods in the context of distance learning. One indicator of student discipline is doing assignments according to teacher instructions. Based on the presentation of observational data, more than 50% of students do not do assignments. The teacher presents a solution through the application of a behavioural approach by giving gifts, motivation, praise, and consequences to overcome this indiscipline. Teacher's love for students is the key and the reason for applying the behaviour approach with the Christian paradigm. The conclusion of this paper, by giving gifts, motivation, praise, and consequences in approaching behaviour with a Christian perspective has been shown to increase student discipline. Suggestions for readers, it is necessary to adjust the form of the stimulus if the teacher teaches students high initiative and tends to be rebellious so that the class can continue effectively.